Literature Review: Overview of Integrated Health Information System Management in Hospitals - Dinda Fidia Ardiani; Daniel Happy Putra; Adi Widodo; Noor Yulia (Rifa'Institute, 2022)
The Health Information System was developed primarily to support health management. The information system used is more focused on a computer-based information system supported by a medical record unit. Electronic Medical Record is the use of information technology devices for collecting, storing, processing and accessing data stored in patient medical records in hospitals in a data-based management system that collects various medical data sources. In managing the health information system, providing access to patient data in digital format, it is hoped that it will make it easier for medical officers to track patient data from time to time, making it easier to obtain patient health information. The process of implementing the system management in this study can be divided into five things, namely: 1.Human Resources, 2.Policies and institutions, 3. System implementation, 4. Data and its management, 5. Access and data integration. This serves to improve the quality of comprehensive health services to patients and medical personnel in helping to provide better health services. In the integrated patient health information system management model, it must provide access to patient health information and allow the exchange of data managed by several medical officers, patient data managers and other hospitals. This is supported by a health information system equipped with a data security system and support from the head of the hospital.